When Might an Assault be so Trivial as to Not Justify a Criminal Conviction? Assault With Intent to do Grievous Bodily Harm, De Minimis Non Curat Lex, and the Case of S v Rahim 2024 JDR 3448 (KZP) - Shannon Hoctor (Obiter, 2024)
As Hall cogently points out, criminal harms differ in gravity: “[F]irst, because of the differential external effect upon the victim and the community … and secondly, by reference to the degree of moral culpability of the offender”. When might criminal conduct be regarded as so trivial as to not be appropriate to visit with the stigma of a conviction? This question engages some important issues concerning criminalisation, and finds practical application in the de minimis non curat lex maxim, which insists that “mere trifles and technicalities must yield to practical common sense and substantial justice”, or to put it in simple terms, that the law does not concern itself with trivial things.This maxim is well-established in South African law, not only finding application in criminal law but also in relation to such fields of law as insolvency, property law, contract and delict. The de minimis maxim certainly fulfils a practical function, in preventing state resources being wasted on inconsequential wrongs, but in the criminal law context, its functioning underscores the need to protect the rights of the individual accused. These rights may be unjustifiably limited by the state, in the context of the exercise of the blunt instrument which the criminal justice system represents, following the commission of a trivial misdeed. In essence, the maxim concerns itself with prosecutability, with deciding whether the “machinery of the criminal law … [ought to be] set in motion”, rather than as a defence excluding unlawfulness. In Snyman’s turn of phrase, prosecution should never amount to persecution. On what is the decision to prosecute (or not) based? In essence, this appears to be a value judgment or policy decision.Feinberg explains that legal coercion should not be used to prevent minor harms, even though in theory a choice to do so would be morally legitimate, because “chances are always good that such a use of power would cause harm to wrongdoers out of all proportion both to their guilt and to the harm they would otherwise cause, even when the priority of innocent interests is taken into account”. This reasoning applies equally to more serious crimes such as kidnapping and assault, and even to the grave crime of assault with intent to do grievous bodily harm, which may be defined as “an assault which is accompanied with the intent to do grievous bodily harm”.The crime of assault with intent to do grievous bodily harm, which is a separate substantive crime rather than merely an aggravated form of assault, consists of the following elements: (i) an assault (that is, following Snyman’s definition, “any unlawful and intentional act or omission (a) which results in another person’s bodily integrity being directly or indirectly impaired, or (b) which inspires a belief in another person that such impairment of her bodily integrity is immediately to take place”; which is (ii) committed with intent to do grievous bodily harm. What constitutes “grievous bodily harm” is a factual question for the courts to decide, but it is clear that the actual infliction of grievous bodily harm is not required for the crime to be committed, but only that the accused intended to commit such harm. In this regard, the practice of listing “grievous bodily harm” as an additional element of the crime is therefore inaccurate and misleading.The application of the de minimis non curat lex maxim to the crime of assault with intent to do grievous bodily harm, and the considerations involved in making such decision, arose for consideration in S v Rahim (2024 JDR 3448 (KZP)).